Design And Analysis Of A Highly Sensitive Hybrid Dispersion-Compensated Erbium-Doped Fiber Amplifier - Jamaludin, Md Zaini (2007)

(untitled)
Optical amplifiers have a great impact on optical communications due to their ability to amplify light along the optical path. Thus optical amplifiers have become indispensable components in high-performance optical communication links. However, while optical amplifiers are effective in mitigating link power loss problems, they are conventionally unusable and irrelevant for another major fiber optic transmission which is dispersion. Compensation of dispersion is a necessity in high speed and/or long distance links. This is separately achieved by use of a dispersion compensator which is either of fiber optics based or fiber Bragg grating based. Thus there is clear need for an integrated system which can achieve both important functions at the same time.New designs have been envisaged and achieved in this thesis. It has shown a great enhancement in performing simultaneous function in amplifying the power as well as compensating the dispersion of the signal (Hybrid). The double-pass erbium-doped fiber amplifier (EDFA) with embedded chirped fiber Brag grating and as well as other filtering technique (optical Bragg grating) have been demonstrated and investigated. It is shown through simulations and by the hardware implementation that the new design is significantly better than that of existing double pass amplifier and double pass amplifier with tunable filter. There are two levels of tests carried out in this study; device level and system (transmission) level. At the device level, the performance parameters of the new configurations are thoroughly characterized showing improvement in gain, noise figure, and the output power, considering the effects of pump power, input signal level, and input signal wavelength. The device configuration is based on double-pass amplification with a Bragg grating employed as the reflector. The grating also serves as a filter suppressing the Amplified Spontaneous Noise from the signal. At the system level, the performance parameters investigated are power sensitivity, power penalty, signal-to-noise ratio (SNR), eye amplitude, eye opening and jitter which all see a level of improvements, based on Wavelength Division Multiplexing (WDM) system.A gain as high as 53.4dB, a noise figure of as low as 5.36dB, and sensitivity of -40dBm have been achieved at the BER of 10-12 for the transmission speed of 2.5Gbps. The new hybrid amplifier provides power gain improvement of 12.5 dB and 8.4 dB for single and multi channel system. The power penalty incurred by the new hybrid amplifier for single and multi channel system are 3.5 dB and 3.2 dB respectively. Comparisons are made against the conventional double pass amplifiers and back-to-back connection.